High-frequency modulation of a quantum-cascade laser using a monolithically integrated intracavity modulator - Hofstetter, Daniel; Beck, Mattias; Aellen, Thierry; Blaser, Stéphane (My University, 2003)
We report a quantum-cascade laser monolithically integrated with an intracavity modulator which could be operated up to 1 GHz. In contrast to earlier approaches, where the radio frequency (RF) modulation signal was supplied to the entire cavity length of the laser structure, we drive only a relatively small 375-/spl mu/m-long section of the cavity. At the same time, a quasi-continuous-wave signal was supplied to the remaining 1125-/spl mu/m-long section. This modulation scheme resulted in smaller parasitic capacitance effects than what we reported previously, and enabled us to work with lower RF voltages and currents.
Keywords: atmospheric window; free-space; intracavity modulator; optical data transmission; quantum-cascade (QC) laser